Em Busca de uma Metodologia: conflitos na definição de identidades - Gonçalves, Matheus Pezzotta (2020)
This work seeks to discuss methodological procedures appropriate to the characteristics and problems resulting from the reminiscences of musical practices in the Quilombo do Carmo Remaining Community located in the municipality of São Roque in the State of São Paulo (Brazil), based on public policies aimed at the musical memory of the municipality. The academic research, through the social practice of writing, promotes knowledge, within the stability of the written object. However, research procedures should consider methodological tools compatible with orality and instability that presents itself in the constant social transformations of the community, in order to contemplate the understanding of identities from their protagonist agents.  Within this context, we use the theoretical orientation of authors such as Sardo to elucidate the concepts of Identity and Music; Bosi and Reily in the field of memories (Collective and Individual); Marchuschi in relation to Orality and Writing. The political systematization of this Cultural Heritage to the detriment of the current legislation, leads to social problems of intense deepening that demand great mobility of agents to revive the cultural practices of that community. In this sense, the Action Research proposed by Tripp presents itself as a methodological procedure that contemplates both the theoretical (academic) and practical demands of the experiences of the object of study. The parallel between musical practices, collective memory and identity is established here.